2013
DOI: 10.1177/0192513x13493277
|View full text |Cite
|
Sign up to set email alerts
|

Is Adoption an Option? The Role of Importance of Motherhood and Fertility Help-Seeking in Considering Adoption

Abstract: Americans have positive views of adoption, yet many never consider adoption. This study examined characteristics that predict whether women ever consider adoption as a pathway to motherhood using an analytic sample of 876 childless women from the National Survey of Fertility Barriers. Using Risman's theory of gender as a social structure as a framework, we focused on the role of the importance of motherhood and infertility in predicting adoption consideration. Women who held higher levels of importance of moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 44 publications
(55 reference statements)
3
34
0
3
Order By: Relevance
“…One of the more common nonmedical response options to infertility is adoption. Although more than 40% of (fertile and infertile) women have considered or are currently considering adoption, only half actually take steps in pursuit of adoption (Park & Wonch Hill, 2014). Those who place greater importance on motherhood and have had prior infertility treatments are more likely to pursue adoption (Park & Wonch Hill, 2014).…”
Section: Alternatives To Infertility Treatmentmentioning
confidence: 99%
“…One of the more common nonmedical response options to infertility is adoption. Although more than 40% of (fertile and infertile) women have considered or are currently considering adoption, only half actually take steps in pursuit of adoption (Park & Wonch Hill, 2014). Those who place greater importance on motherhood and have had prior infertility treatments are more likely to pursue adoption (Park & Wonch Hill, 2014).…”
Section: Alternatives To Infertility Treatmentmentioning
confidence: 99%
“…Choi and colleagues (2005: 177) found that women's expectations were strongly influenced by the 'myth of motherhood' and the lack of alternative mothering discourses produces discrepancy between ideal and reality, giving rise to conflict and frustration. This 'pronatalist' ideology (Park and Wonch-Hill, 2014) provides a strong drive to experience pregnancy and join the 'club', marked by such rites of passage as the growing bump, ante-natal appointments and the 'baby shower'. The transition points are less salient in adoption (Park and Wonch-Hill, 2014: 604):…”
Section: Background Literaturementioning
confidence: 99%
“…junto a la identificación de este perfil sociodemográfico, la literatura especializada ha identificado que la percepción de la población sobre las normas sociales asociadas con la ideología pronatalista (Park y Wonch 2013;Van Laningham et al 2012) y la valoración general hacia los niños (Tyebjee 2003), llevan a que actitudes positivas hacia la adopción concluyan en un comportamiento efectivo. Así, la aceptación y acceso a técnicas de reproducción asistida puede operar como barrera hacia la adopción al tiempo que valoraciones y actitudes más positivas frente a la infancia la propician.…”
Section: Actitudes Y Opiniones De La Población Frente a La Adopciónunclassified